PENINGKATAN KEMAMPUAN PEMASARAN DIGITAL PADA KARANG TARUNA DESA TANAH MERAH SAMPANG - Champaca, Mychelia; Firdausiah, Ayu; Nurhidayat, Moch (FKIP Universitas Wisnuwardhana, 2024)
The global industrial transition to the era of digitalization occurred at the same time as the expansion of the Internet, which had a major impact on this transition during the Covid-19 pandemic. It has been proven that digital marketing initiatives including creating websites, using social media, and using e-commerce platforms strengthen the ability of SMEs to compete. A form of government effort to encourage community activities focused on increasing digitalization to remote areas through academic institutions, whether universities or high schools, and training institutions that intensively explore the issue of digitalization. The important role of entrepreneurship through SMEs has also been shown to be very significant in encouraging the regional economy. Research examining studies on the main topic of marketing digitalization shows the use of digital marketing media such as; electronic commerce, electronic platforms, mobile marketing, e-marketing, and social media. The results of implementing this Community Service activity are in accordance with the objectives to be achieved in this activity, namely, increasing the insight of village youth as measured by responses during participant feedback. The majority of young men and women do not know that digital marketing media can be used to sell any product that has sales value. In addition, some participants who already had products expressed their interest in selling products through the marketplace platform which was conveyed in the activity simulation.